Adaptation of methanol synthesis reactor mathematical model - Лория, Марина Геннадьевна; Абдалхамид, Джабран; Целищев, Алексей Борисович; Елисеев, Петр Иосифович; Захаров, Иван Иванович (Eastern-European Journal of Enterprise Technologies, 2013)
The development of the adaptation algorithm of the model of complex object on the example of methanol synthesis column is discussed in the paper. The main objective of the paper is to develop experimental-statistical models. To create such models it is necessary to have the ability of careful research of the control object, as well as collect quite a large amount of experimental material. For complex control objects, it is sometimes difficult to determine the number of influencing factors and their mutual influence. It is not always possible to use active experiment on the working equipment of continuous and large-scale productions. However, this model has a very simple form. It is easy to use in solving the optimization problems. The paper proposes to use a control system with the combined model for managing multi-shelf gas reactor (e.g. methanol synthesis reactor)